Drinking, drugs and driving in Ireland: more evidence for action. Issue 6 (14th December 2006) - Fitzpatrick, P; Daly, L; Leavy, C P; Cusack, D A
Abstract : Objective: To examine the prevalence of drug positivity among drivers suspected of driving under the influence of an intoxicant, and consequently apprehended by the police in Ireland. Design: 2000 specimens were selected for drug analysis, 1000 with results under the limit for alcohol and 1000 over the limit. The limit for alcohol is 80 mg/100 ml in blood and 107 mg/100 ml in urine. Seven drugs/drug classes were examined; amphetamines, methamphetamines, benzodiazapines, cannabinoids, cocaine, opiates and methadone. Results: 331 (33.1%) of the drivers under the legal limit for alcohol tested positive for one or more of the relevant drugs, and the corresponding figures of drivers over the limit was 142 (14.2%; p<0.001). Using weighted analysis, this corresponds to 15.7% (95% confidence interval (CI) 13.5% to 18.1%) of all tested drivers (15.8% in men and 14.5% in women). Among drivers who had minimal blood alcohol levels, 67.9% (95% CI 61.2% to 74.1%) were taking at least one type of drug. The prevalence of taking drugs reduced steadily as alcohol concentrations increased, but still remained as high as 11.1% (95% CI 8.3% to 14.6%) for drivers with blood alcohol concentrations >200 mg/100 ml. Being under the limit for alcohol, stopped in a city area, stopped between 6 am and 4 pm, or 4 pm and 9 pm, and being of a younger age were each independently associated with drug positivity. Conclusions: There are immediate implications for the evidential breath alcohol program and for checkpoints; in the event of a nil or low alcohol reading being obtained, a separate blood or urine specimen should be sought for analysis, which is currently non-routine.